Ekstrak Daun Pisang Klutuk (Musa balbisiana Colla) sebagai Bahan Tambahan pada Pembuatan Kemasan Aktif berbasis Methyl Cellulose - Safinta Nurindra Rahmadhia; Umar Santoso; Supriyadi Supriyadi (CHEMICA: Jurnal Teknik Kimia, 2019)
The packaging is important in our life. Banana leaf is one of the traditional packaging materials that is widely used because it has wide leaves and is not easily torn. However, traditional packaging has been abandoned by many people, so active packaging needs to be developed that has an advantage of modern and traditional packaging. In this study the active packaging was made based on methylcellulose (MC) which is added by klutuk banana leaf extract (EDPK) and glutaraldehyde (GA). EDPK studied its antioxidant properties and the active packaging was studied for its physical properties. Klutuk banana leaves dried using a cabinet dryer then mashed up and extracted by maceration method using 80% methanol and concentrated with a rotary vacuum evaporator. Then the extract was analyzed for its antioxidant properties. The active packaging/film prepared by casting with the addition of EDPK as an antioxidant and (GA) as a crosslinker agent. EDPK has antioxidant activity 33,17 ± 0,84 %RSA, total phenolic 76,58 ± 7,95 mg GAE/g EDPK and total flavonoids 29.52 ± 4.01 mg QE/g EDPK. The thickness of EDPK films ranged from 0,062-0,080 mm. The FTIR spectrum of EDPK films shows a relatively similar profile in all film formulations.